Digital Printing Training for Design at Students of SMK Budi Karya Natar - Auliya Rahman Isnain; Qadhli Jafar Adrian; Ade Dwi Putra (Journal of Engineering and Information Technology for Community Service, 2023)
The presence of technology in our lives if used positively, actually brings many benefits. No exception to support and maximize a business. Following the rapid development of digital, business competition is getting tougher. Figma is one of the design tools and the advantage of Figma is web based. Illustrations on the figma are created with basic shapes and editing tools available. We can use the edit object to manipulate the nodes as needed. The purpose of the PKM activity entitled introduction to design technology and 3D printing is to provide knowledge to students and teachers about design technology and 3D printing technology and the benefits obtained in the use of design technology and 3D printing. From the results of the questionnaire, knowledge about 3D Printing technology that was distributed before the activity and after the activity there was an increase in student and teacher knowledge about 3D Printing technology from those who knew 50% before the PKM activity, after this activity increased to 100% knowing about 3D Printing technology.